2022
DOI: 10.3390/cancers14092151
|View full text |Cite
|
Sign up to set email alerts
|

Role of Amino Acid Transporter SNAT1/SLC38A1 in Human Melanoma

Abstract: The tumor metabolism is an important driver of cancer cell survival and growth, as rapidly dividing tumor cells exhibit a high demand for energetic sources and must adapt to microenvironmental changes. Therefore, metabolic reprogramming of cancer cells and the associated deregulation of nutrient transporters are a hallmark of cancer cells. Amino acids are essential for cancer cells to synthesize the necessary amount of protein, DNA, and RNA. Although cancer cells can synthesize glutamine de novo, most cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…SLC38A1 (SNAT1) and SLC38A2 (SNAT2) are sodium-dependent neutral amino acid transporters that drive glutamine influx into cells 90 . SLC38A1 is overexpressed in melanoma, breast, gastric, osteosarcoma, and endometrial cancer cells, showing a close association with proliferation and migration [91][92][93] . SLC38A2 is highly expressed in prostate cancer, HCC, and TNBC cells, thereby contributing to tumorigenesis 94,95 .…”
Section: Slc38a1 and Slc38a2mentioning
confidence: 99%
“…SLC38A1 (SNAT1) and SLC38A2 (SNAT2) are sodium-dependent neutral amino acid transporters that drive glutamine influx into cells 90 . SLC38A1 is overexpressed in melanoma, breast, gastric, osteosarcoma, and endometrial cancer cells, showing a close association with proliferation and migration [91][92][93] . SLC38A2 is highly expressed in prostate cancer, HCC, and TNBC cells, thereby contributing to tumorigenesis 94,95 .…”
Section: Slc38a1 and Slc38a2mentioning
confidence: 99%
“…In accordance with these data, ablation of SNAT1 was reported to decrease cell proliferation and migration in melanoma and gastric cancer cell models, evidencing that SNAT1 might play an important role in the maintenance of the malignant phenotype [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 60%
“…Importantly, the expression of SLC38A1 is significantly up-regulated in human melanoma tissue. Knockdown SLC38A1 expression reduce the proliferation rate of melanoma cells [ 29 ]. Consistent with this finding, we found that circTADA2A/CNBP represses the progression of melanoma by inhibiting the SLC38A1expression.…”
Section: Discussionmentioning
confidence: 99%